Cornelius Chase family papers - Chase, Cornelius, 1780-1868.; Chase, Cornelius Thurston, 1819-1870.; Stokes, E. H. (Ellwood Haines), 1815-1897.; Confederate States of America. Army.
Correspondence, journal, speeches, writings, reports, genealogical material, financial records, printed matter, drawings, and other papers relating to Chase family members. Pertains chiefly to Cornelius Chase, and his son, Cornelius Thurston Chase, in their careers as clergymen, educators, and farmers. Documents the latter's career as superintendent of public instruction for the state of Florida. Also includes correspondence of Jonas King and a copy of his interview with Abraham Lincoln.
Collected papers relate to the slave trade in Richmond, Va., and to the slave trading activities of E.H. Stokes, Betts, and Gregory Company; Browning and Moore Company; Dickerson, Hill, and Company; and Moore and Dawson Company. Includes records of the Confederate States of America Army such as reports on Confederate hospitals in Virginia and South Carolina, medical contracts with private physicians in Richmond, Va., provision returns, circulars and special orders relating to the Army's Medical Dept., lists of deserters, quartermaster reports, reports on prisoners of war, and reports on sick and wounded soldiers.
Library of Congress Prints and Photographs Division.
Library of Congress Geography and Map Division.
Clergyman, educator, and farmer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: King, Jonas, -- 1792-1869 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Interviews; Chase family; Confederate States of America. -- Army; Confederate States of America. -- Army -- Supplies and stores; Confederate States of America. -- Army. -- Medical Department; Florida. -- Department of Public Instruction; Browning and Moore Company; Dickerson, Hill, and Company; E.H. Stokes, Betts, and Gregory Company; Moore and Dawson Company; Contracts -- Virginia -- Richmond; Education -- Florida; Military deserters -- Confederate States of America; Military hospitals -- South Carolina; Military hospitals -- Virginia; Physicians -- Employment -- Virginia -- Richmond; Quartermasters -- Confederate States of America; Slave trade -- United States; Slave trade -- Virginia -- Richmond; South Carolina -- History -- Civil War, 1861-1865 -- Hospitals; Virginia -- History -- Civil War, 1861-1865 -- Hospitals; United States -- History -- Civil War, 1861-1865 -- Casualties; United States -- History -- Civil War, 1861-1865 -- Hospitals; United States -- History -- Civil War, 1861-1865 -- Medical care; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Clergy; Educators; Farmers